2006
DOI: 10.1373/clinchem.2005.059535
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Clopidogrel Resistance by Whole Blood Platelet Aggregometry and Inhibitors of the P2Y12 Receptor

Abstract: Background: Inhibition of platelet aggregation by clopidogrel may be insufficient in up to 30% of users. These nonresponders carry an increased risk of cardiovascular events. We reported here a simple assay to study clopidogrel responsiveness. Methods: Electrical impedance aggregometry was performed in diluted whole blood in the presence of 5 and 20 mol/L ADP. Some samples were incubated with 0.1 mmol/L methyl-S-adenosine monophosphate (Me-SAMP), a P2Y 12 receptor blocker, to maximize inhibition of aggregation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 34 publications
3
55
0
2
Order By: Relevance
“…Interestingly, the current results based on a Cox model indicated that female patients had a much higher risk of experiencing ischemic events than did male patients, and a previous study yielded a similar finding. Several studies have indicated that HPR is more prevalent in females than males because of a stronger platelet aggregation reaction to platelet agonist stimulation (13)(14)(15). This might be caused by a high of clotting at the baseline, the effects of female hormone, or a diminished reaction to clopidogrel in female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the current results based on a Cox model indicated that female patients had a much higher risk of experiencing ischemic events than did male patients, and a previous study yielded a similar finding. Several studies have indicated that HPR is more prevalent in females than males because of a stronger platelet aggregation reaction to platelet agonist stimulation (13)(14)(15). This might be caused by a high of clotting at the baseline, the effects of female hormone, or a diminished reaction to clopidogrel in female patients.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in impedance (⍀) is associated with the amount of platelet aggregates deposited on the electrodes after the addition of a platelet agonist (12 ). Details of the aggregometry method have been reported (13 ). We started aggregation by addition of collagen or arachidonic acid (AA), final concentrations 1 mg/L and 0.5 mmol/L, respectively.…”
Section: Aggregometrymentioning
confidence: 99%
“…Such studies are difficult to perform because standardized assays for aggregometry are lacking (6 ). Recently, we validated assays using impedance aggregometry to study the aggregation responses to ASA and clopidogrel (7,8 ). We enhanced the specificity of these assays by in vitro incubation of blood samples with ASA or methyl-S-adenosine monophos-phate (Me-S-AMP), a selective ADP-(P2Y 12 )-receptor blocker.…”
mentioning
confidence: 99%
“…This information is helpful for patient management because platelet inhibition can be improved by increased doses of clopidogrel and/or ASA in patients with a pharmacokinetic resistance. In comparison, pharmacodynamic resistance is less frequent (with a prevalence of approximately 2%) but requires switching to an alternative antiplatelet drug (7,8 ).…”
mentioning
confidence: 99%